Growth rate of the cell populations of the rat sublingual gland during the early postnatal period - Karen F. Madi; Tania M. Cestari; Rumio Tagaa (Brazilian Dental Science)
The development of the rat sublingual gland during the first month of postnatal life was analyzed by morphometry. The absolute number of cells in the various morphological glandular compartments - mixed acini with serous demilunes, intercalated ducts, striated ducts and stroma - was determined by the Aherne II morphometric method for particle counting. The data of fresh glandular volume and the number of cells were analyzed by linear, exponential and parabolic regression, with the best fits being obtained with the linear equation. Based on these equations, the growth rate of glandular volume and of each cell population was calculated. Glandular volume increased about 12-fold during the period from 2 to 30 days of postnatal life, corresponding to a rate of 1.34 mm3/day. This volumetric growth of the gland was mainly due to significant 16-, 10-, 4-, 7- and 8-fold increases in the absolute number of mucous acinar, serous demilune, intercalated duct, striated duct and stromal cells, corresponding to a growth rate of 301 x 103, 228 x 103, 19 x 103, 54 x 103 and 247 x 103 cells/day, respectively. Based on the present results, we conclude that the mucous and serous cell populations of the mixed acini grew at a rate close to that of stromal cells, but considerably higher than that obtained for the intercalated duct and striated duct populations, with the lowest growth rate being observed for the ntercalated duct cell population.